2012
DOI: 10.1016/j.fsi.2011.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization and functional immune response of the carpet shell clam (Ruditapes decussatus) haemocytes after bacterial stimulation

Abstract: The morphology and functionality of Ruditapes decussatus haemocytes have been characterized by light microscopy and flow cytometry, leading to the identification of three different cellular subpopulations. Granulocytes were the largest cells, the hyalinocytes were smaller and contained fewer granules and the intermediate cells showed a size similar to hyalinocytes and a higher number of granules. The phagocytosis of different particles and the associated production of oxygen radicals were measured by flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 89 publications
2
22
1
Order By: Relevance
“…Invertebrate studies have revealed that IAPs play a similar role in this taxon. For example, both live V. splendidus treatments and treatments with a mixture of dead bacteria (Micrococcus luteus, V. splendidus, and V. anguillarum) increased IAP expression in the carpet shell clam (Ruditapes decussatus) (Prado-Alvarez et al, 2012). In addition, previous study demonstrated that CgIAP1 transcript levels increased soon after a V. anguillarum challenge and reached the highest expression at 12 h in the Pacific oyster (Zhang et al, 2011).…”
Section: Cgiap2-mediated Regulation Of Innate Immune Responsementioning
confidence: 87%
“…Invertebrate studies have revealed that IAPs play a similar role in this taxon. For example, both live V. splendidus treatments and treatments with a mixture of dead bacteria (Micrococcus luteus, V. splendidus, and V. anguillarum) increased IAP expression in the carpet shell clam (Ruditapes decussatus) (Prado-Alvarez et al, 2012). In addition, previous study demonstrated that CgIAP1 transcript levels increased soon after a V. anguillarum challenge and reached the highest expression at 12 h in the Pacific oyster (Zhang et al, 2011).…”
Section: Cgiap2-mediated Regulation Of Innate Immune Responsementioning
confidence: 87%
“…The other cells were treated with 1 mL of N-acetyl-L-cystein (NAC) and pyrrolidine dithiocarbamate (PDTC) from Sigma (1 mM and 50 µM, respectively) for 1 h before UV treatment, as these components were scavengers of oxygen free radicals that directly interacted with reactive oxygen species. Immediately after 45 min irradiation, the production of ROS was measured using a 2′,7′-dichlorofluorescein-diacetate probe (DCFH-DA, Molecular Probes) through flow cytometry according to the protocol of Prado-Alvarez et al [40]. Cell Quest software (B&D) was used to determine the mean of fluorescence of 10,000 events in the R1 (granulocytes) and R2 (hyalinocytes) regions.…”
Section: Methodsmentioning
confidence: 99%
“…galloprovincialis and the clam Ruditapes philippinarum [17,55]. In our study, whatever was the origin of the oysters and the tested conditions, cells identified by flow cytometry as hyalinocytes were more abundant than cells identified as granulocytes.…”
Section: Discussionmentioning
confidence: 48%